DUT Guide on Supervision - Gitte Wichmann-Hansen (Dansk Universitetspædagogisk Netværk, 2021)
The aim of this guide is to provide tips for supervisors on how to support students as active, independent and prepared participants who drive their own projects forward. It relates to supervision of projects at bachelor-, master- and PhD level. The underlying basis of the guide is twofold: 1) supervision is an increasingly complex activity that involves a demanding set of competences; 2) a good supervisor is a flexible supervisor who can adapt to different situations, student needs and levels of the curriculum.